Pengolahan Sampah Polimer Termoplastik dan Termoset di Lingkungan Bank Sampah Induk Kabupaten Jember - Shofiyah, Rohimatush; Irawati, Irawati (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2024)
The Jember Regency Main Garbage Bank has the role of fostering and coordinating the Unit Garbage Bank in the Jember Regency area. BSI had several problems in terms of how to sort polymer waste and the need for technological tools for processing plastic polymer waste. The purpose of the PKM activity is to convey knowledge, information and technology for processing plastic polymer waste. The socialization that has been delivered is related to thermoplastic and thermoset polymer waste processing technology based on physical, chemical, technological and mechanical properties, as well as management and marketing strategy for waste bank products. After interviews with BSI and BSU management, discussions with participants, mentoring, and evaluation with partners; The PKM team presented that a Garbage Bank in the city of Jember really needs a plastic polymer waste counting tool to realize the Zero Waste program, increase economic value, usability and aesthetic value. Processing of plastic polymer waste has several methods, namely; recycling plastic waste into handicraft products, turning plastic waste into pellets, processing plastic waste into; fuel oil, brick mixture, and asphalt, recycling process, namely; Hydrogenation, Glycolysis, Methanolysis, Hydrolysis, Gasification, Pyrolysis and Catalytic Conversion, Recycling methods, namely (primary, secondary, tertiary and quarter) recycling.